1979
DOI: 10.1149/1.2129109
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Iron Sulfide  ( Fe1 − δ  S  )  Scale on Iron at Temperatures 600°–1000°C

Abstract: Measurements of the parabolic sulfidation kinetics were carried out at sulfur pressures ranging from i0 -Iz to 10 -2 arm and at temperatures in the range 600~176The effect of sulfur activity on these kinetics is most pronounced at low sulfur pressures. Temperature exhibits the largest influence on these kinetics at high sulfur pressures. An expression is derived for the parabolic rational rate constant in terms of the chemical diffusivity and nonstoichiometry of iron sulfide using the Wagner equation for scali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 10 publications
6
22
0
Order By: Relevance
“…The best-fit error function solutions are overlaid on top of experimental data with a range of uncertainty in Fig.4. †Increased diffusion activation energy from spontaneous magnetizationValues of *D Fe obtained from error function fitting are shown in Arrhenius form in Fig.5, alongside representative literature results from Fryt et al10 and Condit et al,14 whose data are also displayed in Fig.1. † We include for comparison only those data corresponding to the stoichiometry range 0.03 r x r 0.1 in Fe 1Àx S, which is close to the composition of our samples analyzed via SIMS.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…The best-fit error function solutions are overlaid on top of experimental data with a range of uncertainty in Fig.4. †Increased diffusion activation energy from spontaneous magnetizationValues of *D Fe obtained from error function fitting are shown in Arrhenius form in Fig.5, alongside representative literature results from Fryt et al10 and Condit et al,14 whose data are also displayed in Fig.1. † We include for comparison only those data corresponding to the stoichiometry range 0.03 r x r 0.1 in Fe 1Àx S, which is close to the composition of our samples analyzed via SIMS.…”
supporting
confidence: 60%
“…Fig.5Values for iron self-diffusion coefficient *D Fe results obtained in this work are compared to data from Fryt et al10 and Condit et al14 The known magnetostructural ordering (Ne ´el) temperature T N of 316 1C is indicated with a dashed line. Above T N the activation energy slope in the paramagnetic state is Q P = 0.83 AE 0.03 eV.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The Fe/S ratio is known as a function of Sulfur pressure for this material, see Fryt et aZ. (1). When iron specimens were sulfidized to completion in our apparatus at the pressures used in our study, the Fe/S ratios compiled and reported by Fryt et aI.…”
Section: Methodsmentioning
confidence: 66%
“…This result is in agreement with results of the electrochemical experiments: the anodic branch of the linear polarisation experiments does not show formation of a protective layer (though layer formation clearly takes place), and the charge transfer resistance determined by EIS is low. Indeed, several studies have shown that FeS films behave as metallic conductors [62,5]. Computational studies of mackinawite also indicate a metallic behaviour for at least one spin channel [63][64][65][66].…”
Section: Discussion Of the Nature Of Corrosion Productsmentioning
confidence: 99%